Formulation Evaluation and Comparative Study of Herbal Mouthwash with Marketed Preparation - Aman Mohata; Seema Wakodkar; Jagdish Baheti (Asian Journal of Pharmaceutical Research and Development, 2024)
The current study aims to create and assess a herbal mouthwash and assess its efficacy in combating the oral cavity's microbial load. To extract the hydroalcoholic and water-soluble components, plant materials were gathered. Piper nigrum seeds and hibiscus flowers were used to prepare herbal mouthwash for extraction. The prepared mouthwash's pH, antibacterial activity, and physicochemical characteristics were further assessed. The mouthwash that is currently available has good antibacterial qualities. Currently, available mouthwash is a liquid formulation that often includes antiseptic and antibacterial ingredients. The major benefits of utilizing mouthwashes are that they can be used regularly at home to maintain good oral hygiene, that they have antibacterial activity, that they can be used as prophylaxis before and after oral surgery procedures like tooth extractions, and that they clean teeth after brushing. These solutions may be used for various purposes, such as their analgesic, anti-inflammatory, or anti-fungal properties, in addition to their ability to lessen microbial development, gingivitis, and halitosis in the oral cavity.